Use of an electronic information system to identify adverse events resulting in an emergency department visit. Issue 6 (10th August 2010) - Ackroyd-Stolarz, Stacy; MacKinnon, Neil J; Zed, Peter J; Murphy, Nancy
Abstract : Objective: There is limited information about the nature of adverse events (AEs) that necessitate an emergency department (ED) visit. The objective of the current study was to demonstrate the feasibility of using routinely collected electronic data to identify AEs in patients presenting to EDs in one Canadian health authority. Methods: This retrospective cross-sectional study occurred in EDs in two community hospitals, an outpatient community health centre and a tertiary care facility in the Capital District Health Authority in Nova Scotia, Canada between 1 November 2007 and 31 October 2008. The primary outcome was identification of an AE as the main reason for the ED visit. AEs were identified from electronic diagnostic data using previously validated screening criteria. Results: There were 142 433 patient visits to the four EDs during the study period. A total of 1870 (1.3%) AEs were identified using the screening criteria. This included 1133 (0.8%) procedure-related, 673 (0.5%) drug-related, 63 (0.04%) device-related and one radiation-related AE. The AEs identified using this method were most likely the manifestation of treatment decisions made prior to the ED visit and/or related to care in other settings (eg, primary or long-term care, acute hospital care) including previous ED visits. Interpretation: Although the use of electronic data significantly underestimates AEs treated in the ED, for relatively low cost, it provides new information on AEs arising from a variety of care settings that may otherwise not be captured. Significant and clinically important differences in healthcare utilisation underscore the value in identifying these AEs.